Implementation and initial clinical experience of offline PET/CT-based verification of scanned carbon ion treatment - Bauer, Julia; Unholtz, Daniel; Sommerer, Florian; Kurz, Christopher; Haberer, Thomas; Herfarth, Klaus; Welzel, Thomas; Combs, Stephanie; Debus, Jürgen; Parodi, Katia (Radiotherapy and oncology, 2013)
Background and purpose - We report on the implementation of offline PET/CT-based treatment verification at the Heidelberg Ion Beam Therapy Centre (HIT) and present first clinical cases for post-activation measurements after scanned carbon ion irradiation. Key ingredient of this in-vivo treatment verification is the comparison of irradiation-induced patient activation measured by a PET scanner with a prediction simulated by means of Monte Carlo techniques. - Material and methods - At HIT, a commercial full-ring PET/CT scanner has been installed in close vicinity to the treatment rooms. After selected irradiation fractions, the patient either walks to the scanner for acquisition of the activation data or is transported using a shuttle system. The expected activity distribution is obtained from the production of β+-active isotopes simulated by the FLUKA code on the basis of the patient-specific treatment plan, post-processed considering the time course of the respective treatment fraction, the estimated biological washout of the induced activity and a simplified model of the imaging process. - Results - We present four patients with different indications of head, head/neck, liver and pelvic tumours. A clear correlation between the measured PET signal and the simulated activity pattern is observed for all patients, thus supporting a proper treatment delivery. In the case of a pelvic tumour patient it was possible to detect minor treatment delivery inaccuracies. - Conclusions - The initial clinical experience proves the feasibility of the implemented strategy for offline confirmation of scanned carbon ion irradiation and therefore constitutes a first step towards a comprehensive PET/CT-based treatment verification in the clinical routine at HIT.